2016
DOI: 10.1080/19443994.2014.986528
|View full text |Cite
|
Sign up to set email alerts
|

Study on the treatment of wastewater containing Cu(II) by D851 ion exchange resin

Abstract: A static adsorption experiment of copper ion was performed with D851 ion exchange resin to determine some optimum treatment parameters. The results of the experiment showed that the enthalpy value of the reaction was positive and the optimum reaction time was 60 min, while the optimum pH value and reaction temperature were 5.5 and 35˚C, respectively. The adsorption equilibrium density of 0.1 g ion exchange resin was between 75 and 100 mg/L. With the condition of the hydraulic retention time of 60 min, wastewat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…We then explored the traditional regeneration efficiency of saturated GA–Cu 2+ , as shown in Figures b–d. The conventional regeneration method for metal ion adsorbents generally requires a high concentration of hydrochloric acid of >100 mM. , For comparison, GA was regenerated by 100 mM HCl, and the results in Figure b indicated that the initial collected effluent concentration of Cu 2+ was as high as 260.5 mg L –1 with [Cu 2+ ] eff /[Cu 2+ ] in = 40.4, suggesting that adsorbed Cu 2+ was exchanged with excess H + and that the recovery ratio was nearly 100%. However, the ratio of influent H + versus the desorbed Cu 2+ , H + inf /Cu 2+ desorb , was close to 200, indicating that H + must be in large excess for thorough Cu 2+ desorption (Figure c), and the pH value, ∼1.0, of the effluent solution is too low (Figure d) to discharge into the environment.…”
Section: Resultsmentioning
confidence: 99%
“…We then explored the traditional regeneration efficiency of saturated GA–Cu 2+ , as shown in Figures b–d. The conventional regeneration method for metal ion adsorbents generally requires a high concentration of hydrochloric acid of >100 mM. , For comparison, GA was regenerated by 100 mM HCl, and the results in Figure b indicated that the initial collected effluent concentration of Cu 2+ was as high as 260.5 mg L –1 with [Cu 2+ ] eff /[Cu 2+ ] in = 40.4, suggesting that adsorbed Cu 2+ was exchanged with excess H + and that the recovery ratio was nearly 100%. However, the ratio of influent H + versus the desorbed Cu 2+ , H + inf /Cu 2+ desorb , was close to 200, indicating that H + must be in large excess for thorough Cu 2+ desorption (Figure c), and the pH value, ∼1.0, of the effluent solution is too low (Figure d) to discharge into the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Eqs. (8) 、(9) were used to calculate the thermodynamic parameters for the adsorption of Cu (II) onto the D401 resin, including ΔG (kJ·mol −1 ), ΔS (J·mol −1 ·K −1 ) and ΔH (kJ·mol −1 ), were calculated with the following equations( He et al, 2014 ): where R (8.314 J/mol · K) is the gas constant, T (K) stands for the absolute temperature, and K L (L/mg) is the standard thermodynamic equilibrium constant defined by Q e / C e The values ΔH and ΔS can be calculated from the slope and intercept of Vant's Hoff plots of ln K L vs T / 1.…”
Section: Methodsmentioning
confidence: 99%
“…There are several processes used for wastewater polluted with heavy metal ions like chemical precipitation techniques [17,18], membrane processes [19,20], electro dialysis [21], ion exchange process [22], flotation [23], extraction [24], and adsorption [25,26]. Adsorption is considered a meaningful and good alternative from an economic view due to its simplicity, availability, and low cost [27,28].…”
Section: Introductionmentioning
confidence: 99%